Fluorescein dihexanoate as a profluorescent marker for monitoring of hydrolytic descruction of polylactide-based materials - Belov, Dmitry A.; Faletrov, Yaroslav V.; Yakovets, Polina S.; Shkumatov, Vladimir M. (Journal of the Belarusian State University. Chemistry, 2022)
Polylactide (PLA) is one of the most promising biodegradable and biocompatible polymer materials. Estimation of hydrolytic destruction of PLA is of high importance for their applications both at planning and at real-time exploitation. This paper reports on synthesis and applicability of fluorescein-O-dihexanoate as a pro-fluorescent marker of hydrolytic destruction of two types of PLA-based materials. Fluorescence enhancement correlated with adequately more fast destruction of poly-D,L-lactide as well as less stability to alkaline hydrolysis. Thus, applicability of fluorescein-O-dihexanoate for fluorescence-based estimation of hydrolytic destruction of PLA-based materials is shown in quite real time mode.
Keywords: poly-L-lactide; poly-D,L-lactide; fluorescein-O-dihexanoate; fluorescence; hydrolysis